2000
DOI: 10.1093/jexbot/51.350.1563
|View full text |Cite
|
Sign up to set email alerts
|

Control of abscisic acid synthesis

Abstract: The abscisic acid (ABA) biosynthetic pathway involves the formation of a 9-cis-epoxycarotenoid precursor. Oxidative cleavage then results in the formation of xanthoxin, which is subsequently converted to ABA. A number of steps in the pathway may control ABA synthesis, but particular attention has been given to the enzyme involved in the oxidative cleavage reaction, i.e. 9-cis-epoxycarotenoid dioxygenase (NCED). Cloning of a gene encoding this enzyme in maize was first reported in 1997. Mapping and DNA sequenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
136
0
20

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 250 publications
(161 citation statements)
references
References 51 publications
5
136
0
20
Order By: Relevance
“…A redução na condutância se deve ao decréscimo na disponibilidade de água no solo, que ocasiona queda no potencial da água nas folhas, levando-as à perda de turgescência e à redução da condutância estomática (Paiva et al, 2005). Outra explicação é a sinalização proporcionada pelo ácido abscísico produzido no sistema radicular, induzindo o fechamento dos estômatos presentes nas folhas (Taylor et al, 2000), reduzindo assim a condutância estomática. A utilização de caracteres morfológicos aliados ao rendimento de frutos pode fornecer os subsí-dios necessários para identificação de plantas com maior resistência ao déficit hídrico.…”
Section: Resultsunclassified
“…A redução na condutância se deve ao decréscimo na disponibilidade de água no solo, que ocasiona queda no potencial da água nas folhas, levando-as à perda de turgescência e à redução da condutância estomática (Paiva et al, 2005). Outra explicação é a sinalização proporcionada pelo ácido abscísico produzido no sistema radicular, induzindo o fechamento dos estômatos presentes nas folhas (Taylor et al, 2000), reduzindo assim a condutância estomática. A utilização de caracteres morfológicos aliados ao rendimento de frutos pode fornecer os subsí-dios necessários para identificação de plantas com maior resistência ao déficit hídrico.…”
Section: Resultsunclassified
“…Studies have suggested that the stress that is caused by drought and decreased cell volume during desiccation induces the accumulation of ABA [21] [22]. In this way, many of the physiological and biochemical changes caused by ABA in developing embryos can be induced by low osmotic potential [18].…”
Section: Resultsmentioning
confidence: 99%
“…ABA accumulates under hyperosmotic conditions and triggers the closure of guard cells (to prevent water loss) in consonance with expression of ABA-specific stress responsive genes (Leung and Giraduat, 1998;Taylor et al, 2000;Wilkinson and Devis, 2002). Also, ABA independent signaling pathways are activated (Ingram and Bartels, 1996).…”
Section: Abscisic Acid (Aba) and Stressmentioning
confidence: 99%